Superradiant Instability of D-Dimensional Reissner-Nordstrom Black Hole Mirror System - 李然 赵俊坤 张延明 (Communications in theoretical physics, 2015)
We analytically study the superradiant instability of charged massless scalar field in the background of D-dimensional Reissner-Nordstr6m （RN） black hole caused by mirror-like boundary condition. By using the asymptotic matching method to solve the Klein-Gordon equation that governs the dynamics of scalar field, we have derived the expressions of complex parts of boxed quasinormal frequencies, and shown they are positive in the regime of superradiance. This indicates the charged scalar field is unstable in D-dimensional Reissner-Nordstr6m （RN） black hole surrounded by mirror. However, the numerical work to calculate the boxed quasinormal frequencies in this system is still required in the future.